2015
DOI: 10.5812/jjm.16058
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Benzalkonium Chloride on Planktonic Growth and Biofilm Formation by Animal Bacterial Pathogens

Abstract: Background:Resistance toward quaternary ammonium compounds (QACs) is widespread among a diverse range of microorganisms and is facilitated by several mechanisms such as biofilm formation.Objectives:In this study, the effects of benzalkonium chloride on planktonic growth and biofilm formation by some field isolates of animal bacterial pathogens were investigated.Materials and Methods:Forty clinical isolates of Escherichia coli, Salmonella serotypes, Staphylococcus aureus and Streptococcus agalactiae (10 isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…A second issue is the aging of biofilms. Most researchers have investigated the activity of antimicrobial agents against young bacterial biofilms, created over 24 h [ 38 , 43 , 48 ] or 48–72 h [ 49 , 50 ]. Only some studies have used biofilms created over several days [ 32 , 36 , 39 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…A second issue is the aging of biofilms. Most researchers have investigated the activity of antimicrobial agents against young bacterial biofilms, created over 24 h [ 38 , 43 , 48 ] or 48–72 h [ 49 , 50 ]. Only some studies have used biofilms created over several days [ 32 , 36 , 39 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ebrahimi et al. showed that benzalkonium chloride at concentrations higher than the MIC have no further effects on growth and biofilm formation of planktonic cells [ 29 ]. Currently, there is limited evidence about biofilm formation and its mechanism at sub-MICs of antimicrobial agents.…”
Section: Discussionmentioning
confidence: 99%
“…Increased rates of replication (Andersson and Hughes 2009 , 2011 ) and mutation (Cortes et al 2008 ; Morero et al 2011 ; Thi et al 2011 ; Gutierrez et al 2013 ; Chow et al 2015 ) have also been evidenced. Moreover, low concentrations contribute to signalling molecules for biofilm formation and gene expression (Andersson and Hughes 2014 ; Aka and Haji 2015 ; Ebrahimi et al 2015 ). As such, sub-lethal concentrations could stimulate the spread of resistance in the environment and increase the likelihood of multi-resistant bacteria through genetic changes (Sandegren 2014 ).…”
Section: Introductionmentioning
confidence: 99%